The Use of Running Dictation Technique to Improve Students’ Listening Skill - Melya Destiana; Syamsul Bahri; Nurul Inayah (Research in English and Education Journal, 2019)
Listening is one of challenging skills for EFL students. However, limited attention in the classroom was given to improve the skill. A preliminary study at VIII-4 class of MTsN Model Banda Aceh revealed that there were 3 main listening difficulties faced by the students. Those are listening for details, unfamiliar sounds and vocabulary. Since most of the students (18 out of 35 students) experienced difficulty in listening for details, this study focused to improve the listening for detail sub skill by applying running dictation. The sample in this study was taken by using purposive sampling. The writer chose the students of preliminary study as the sample. There were 35 students participated in this study. The result of the study revealed that after being taught by using running dictation, the students’ score in listening for details improves significantly. The mean score of pretest 35.43 goes up sharply to 86.29 in the posttest. It means that running dictation increase students’ score 50.86 points. Furthermore, the analysis of t-test showed that tscore ttable or 13.12 1.69 (tscore greater than ttable). It could be concluded that the alternative hypothesis (Ha) is accepted. It thus, can be said that running dictation can be one of way to improve the listening for details sub skill in listening classroom.